Implementation popular science book development of herbal planting in an attempt to settle the student's senior high school critical thinking skills - Nurul Ishthifaiyah; Muhammad Zaini; Badruzsaufari Badruzsaufari (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
Critical thinking skills are one of the skills to have in the 21st century. The realities of learning that are still applying learning teachers-centered, teachers deliver biology as products and learners memorize factual information. Popular scientific books become one of the means that can be used to settle critical thinking skills. In this study developed popular type scientific books and utilization of plant mental in the village official. This study aims to describe the practicality of popular scientific book expectations developed to improve the critical thinking skills of learners. This research is a development research with formative evaluation that uses the design of Tessmer. The subject of research is 7 students learned for practical and effectively tests. The results showed that the popular scientific books developed were categorized as very practical with a percentage of 100% and received a very good response from students with a percentage of 88.9%. The results of the effectiveness of expectations are categorized as high and there is an increase from meetings 1 to 3 with an average percentage of 81.7%. These results indicate that the popular scientific books developed are very practical and effectively used in training high school students' critical thinking skills.Abstrak Kemampuan berpikir kritis merupakan salah satu kemampuan yang harus dimiliki di abad 21. Realita pembelajaran yang terjadi saat ini masih menerapkan pembelajaran yang berpusat pada guru yang menyampaikan Biologi sebagai produk dan peserta didik hanya menghafal informasi faktual. Untuk itu, penelitian ini bertujuan guna mengembangkan buku ilmiah populer jenis dan pemanfaatan tanaman jamu di Kampung Pejabat sebagai sarana alternatif untuk student centered learning sekaligus melatihkan kemampuan berpikir kritis. Penelitian ini mengembangkan buku ilmiah populer jenis dan pemanfaatan tanaman jamu di Kampung Pejabat. Penelitian ini merupakan penelitian pengembangan dengan evaluasi formatif Tessmer. Subjek penelitian adalah 7 orang peserta didik dengan analisis statistik deskriptif menggunakan uji kepraktisan harapan dan keefektifan harapan. Hasil penelitian menunjukkan buku ilmiah populer yang dikembangkan terkategori sangat praktis dengan persentase sebsesar 100%dan mendapatkan respon yang sangat baik dari siswa dengan persentase sebesar 88,9%. Hasil keefektifan harapan terkategori tinggi dan terjadi peningkatan dari pertemuan 1 sampai 3 dengan rata-rata persentase sebesar 81,7%. Hasil ini menunjukkan bahwa buku ilmiah populer yang dikembangkan sangat praktis dan efektif digunakan dalam melatihkan kemampuan berpikir kritis siswa SMA.